2021
DOI: 10.1590/1518-8345.4461.3456
|View full text |Cite
|
Sign up to set email alerts
|

Use of a therapeutic communication application in the Nursing undergraduate program: randomized clinical trial

Abstract: Objective: to analyze the effect on the knowledge of therapeutic communication by Nursing students through the use of applications. Method: a randomized and controlled clinical trial conducted with 60 nursing students. In the topic Groups and therapeutic communication techniques, the intervention-IG group (n=30) used the application and the control-CG group (n=30) was submitted to the traditional class. The pre- (Zero Test -0) and post-test knowledge (immediate-Test 1 and after 30 day-Test 2) of those involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
(27 reference statements)
1
8
0
2
Order By: Relevance
“…The current study revealed an increase in the medians of correct answers from P0 to P2. These same results were found in a randomized controlled clinical trial conducted in northeastern Brazil, which pointed out that the mean of the scores after the intervention increased, especially in the intervention group, showing an effect on the knowledge of students who used an app on therapeutic communication (14) .…”
Section: Itemssupporting
confidence: 79%
See 3 more Smart Citations
“…The current study revealed an increase in the medians of correct answers from P0 to P2. These same results were found in a randomized controlled clinical trial conducted in northeastern Brazil, which pointed out that the mean of the scores after the intervention increased, especially in the intervention group, showing an effect on the knowledge of students who used an app on therapeutic communication (14) .…”
Section: Itemssupporting
confidence: 79%
“…Nurse educators and researchers should collaborate in the development of virtual learning resources to support Clinical Nursing teaching (13) . Given the suggestions, it is recommended, in a future time, to verify the repercussions of using the app in the clinical practice on various health issues and with larger samples and longer follow-ups (14) .…”
Section: Itemsmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 A randomized clinical trial has demonstrated that apps can facilitate contemporary teaching, calling on professionals to develop, validate, and use technology for teaching. 4 Nurses and researchers have invested in developing apps to support different dimensions of care for people in social isolation, especially in recent years. 5 Despite this, to the best of our knowledge, no app exists for diabetes education during the COVID-19 pandemic.…”
mentioning
confidence: 99%